2015
DOI: 10.1037/prj0000088
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurring mental illness, substance use disorders, and antisocial personality disorder among clients of forensic mental health services.

Abstract: Forensic mental health services must take into account the effect that co-occurring disorders have on clients' functioning and offending. Those who work with people with psychiatric disabilities and co-occurring substance use disorders must ensure that the substance disorders are addressed to help ensure recovery from the mental illness and to reduce the likelihood of offending. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 37 publications
5
45
0
1
Order By: Relevance
“…In consequence of the study, it has been observed that the most frequent psychiatric disorder is anxiety and adjustment disorders (45.7%), and that the repetitive offenders mostly fall under the 2nd axis diagnosis criteria of cluster B (borderline and antisocial personality disorder) based on the DSM-IV classification system, and that those who suffer from alcohol and substance-use disorder have committed more repetitive crimes. The findings are in compliance with the literature; it has been indicated that more frequent and serious crimes have been committed in the comorbid condition, where psychiatric disorder is combined with substance use and antisocial personality disorder, in comparison with those who suffer from only psychiatric disease [27]. Oncu et al have reported a comorbid condition in 25% of forensic psychiatric cases committing recurrent offenses after compulsory clinical treatment, and they have also reported that 75% of them have personality disorder and/or alcohol substance-use disorder [24].…”
Section: Discussionsupporting
confidence: 89%
“…In consequence of the study, it has been observed that the most frequent psychiatric disorder is anxiety and adjustment disorders (45.7%), and that the repetitive offenders mostly fall under the 2nd axis diagnosis criteria of cluster B (borderline and antisocial personality disorder) based on the DSM-IV classification system, and that those who suffer from alcohol and substance-use disorder have committed more repetitive crimes. The findings are in compliance with the literature; it has been indicated that more frequent and serious crimes have been committed in the comorbid condition, where psychiatric disorder is combined with substance use and antisocial personality disorder, in comparison with those who suffer from only psychiatric disease [27]. Oncu et al have reported a comorbid condition in 25% of forensic psychiatric cases committing recurrent offenses after compulsory clinical treatment, and they have also reported that 75% of them have personality disorder and/or alcohol substance-use disorder [24].…”
Section: Discussionsupporting
confidence: 89%
“…An estimated 50 to 66% of offenders meet DSM-IV criteria (American Psychiatric Association 2000) for substance abuse or dependence, whereas only 9% of the general population meet these criteria (Mumola and Karberg 2006). In a sample of clients in forensic mental health services, 78% met the criteria for at least one lifetime substance use disorder diagnosis (Ogloff et al 2015). The association between substance use and offending behavior can be explained by several reasons including that substance use may exacerbate psychological symptoms (Swanson et al 2008), thereby increasing the likelihood of offending behavior (Giancola 2004).…”
Section: Introductionmentioning
confidence: 99%
“…There is an issue that many addicts or mentally ill also develop antisocial behavior as a symptom of the addictive or mental illness processes [17]. These symptoms are not prior to the addiction or mental illness onset and after recovery they do NOT exhibit the antisocial behavior (which would not be true of the APDs).…”
Section: Problem-solving Courts and Beyondmentioning
confidence: 99%
“…The symptoms include lack of a conscience or sense of guilt, lack of empathy, egocentricity, pathological lying, repeated violations of social norms, and disregard for the law, shallow emotions, and a history of victimizing others [16]. A related clinical, research, and a diagnostic issue is that many anti-social personality disordered individuals (APD) also have addictive disorders or other symptoms of mental illnesses but which perhaps is still part of their larger psychopathological personality or criminal personality [17]. These individuals will prey on others until stopped.…”
Section: Problem-solving Courts and Beyondmentioning
confidence: 99%